Where's all the 'good' sports journalism? Sports media research, the sociology of sport, and the question of quality sports reporting. (September 2018) - Weedon, Gavin; Wilson, Brian; Yoon, Liv; Lawson, Shawna
Across newsrooms and journalism schools, questions as to what constitutes or 'counts' as excellent reporting are currently inciting much debate. Among the various frameworks being put forward to describe and encourage 'excellent' journalism in its various forms, sport is seldom mentioned – a legacy perhaps of its perennial dismissal as trivial subject matter. This essay grew from our curiosity as to whether the reverse was also true: that is, whether and what those who study sports journalism and sports media – in particular sociologists of sport – have contributed to understandings of 'best' and even excellent journalistic practice. We identified and analysed 376 articles from eight leading scholarly journals that feature sports media research with the aim of examining instances where 'excellent' sports reporting was either highlighted, described or advocated. After outlining the major themes that emerged from this analysis, we reflect on why so few of the sampled articles explicitly advise on what best practice sports journalism might look like – especially when it comes to coverage of the sport-related social issues that sociologists of sport tend to focus on – and why so little theoretical attention has been afforded to the question of excellent sports journalism more generally. While there are good sociological reasons for focusing on problematic sports reporting, on structural and systemic issues in which media are implicated, and on producing alternatives to hegemonic sports media, we conclude that it is high time for instances of excellent sports journalism to be afforded the theoretical and empirical attention long granted to their 'bad' journalistic counterparts.